Desert dancer - Farley, Terri (New York, N.Y. : Avon Books, 2003)
The Phantom's lead mare is missing and when Sam finds the mare in government custody she is desperate to set her free. But the mare is badly injured and could put the herd at risk. How far should Sam go to help the horses she loves?
Ages 10 up.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Ranch life -- Juvenile fiction; Horses -- Fiction; Ranch life -- Fiction